2020
DOI: 10.3390/microorganisms8020220
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dose and Timing of Burdock (Arctium lappa) Root Intake on Intestinal Microbiota of Mice

Abstract: Water-soluble dietary fiber such as inulin improves the beta diversity of the intestinal microbiota of mice fed with a high-fat diet (HFD). The circadian clock is the system that regulates the internal daily rhythm, and it affects the pattern of beta diversity in mouse intestinal microbiota. Burdock (Arctium lappa) root contains a high concentration of inulin/fructan (approximately 50%) and is a very popular vegetable in Japan. Arctium lappa also contains functional substances that may affect intestinal microb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 57 publications
3
13
0
1
Order By: Relevance
“…In vivo it was established that the relative count of Bifidobacterium and Lactobacillus increased in an A. lappa group of mice compared with cellulose and commercial inulin groups. At the same time, a slight increase in the Staphylococcus concentration was detected in the inulin group compared with the A. lappa and cellulose groups [ 50 ]. However, as indicated in the study above with extracts, and even more so with plant flour, the effect on microorganisms may affect not only prebiotics but also growth inhibitors (for example, phenolic compounds).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo it was established that the relative count of Bifidobacterium and Lactobacillus increased in an A. lappa group of mice compared with cellulose and commercial inulin groups. At the same time, a slight increase in the Staphylococcus concentration was detected in the inulin group compared with the A. lappa and cellulose groups [ 50 ]. However, as indicated in the study above with extracts, and even more so with plant flour, the effect on microorganisms may affect not only prebiotics but also growth inhibitors (for example, phenolic compounds).…”
Section: Discussionmentioning
confidence: 99%
“…16S rDNA obtained from the fecal extraction was analyzed by Illumina sequencing according to the 16S Metagenomic Sequencing Library Preparation (15044223 B) protocol. The experimental method of 16S rDNA sequencing was described by Watanabe et al (2020) . The DNA library was sequenced using MiSeq Reagent Kit V3 (Illumina Inc.) in the MiSeq platform according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Cecal SCFA concentrations were calculated as µmol/mg of dry cecal weight. This procedure of quantitative SCFA and lactic acid analysis was established in our papers [37,38,40].…”
Section: Measuring the Scfa And Lactic Acid Levels In The Cecummentioning
confidence: 99%
“…Likewise, the study on effective nutrient intake timing in relation to the biological circadian rhythm is called chrononutrition. Previous studies have shown the importance of chronopharmacology and chrononutrition [36][37][38].…”
Section: Introductionmentioning
confidence: 99%